-5c+6=-29

Simple and best practice solution for -5c+6=-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5c+6=-29 equation:


Simplifying
-5c + 6 = -29

Reorder the terms:
6 + -5c = -29

Solving
6 + -5c = -29

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -5c = -29 + -6

Combine like terms: 6 + -6 = 0
0 + -5c = -29 + -6
-5c = -29 + -6

Combine like terms: -29 + -6 = -35
-5c = -35

Divide each side by '-5'.
c = 7

Simplifying
c = 7

See similar equations:

| 14=-(p-8)+2 | | 6x+3=4x-8 | | 1000=x*(1+0,45) | | 3(3a-5)=60 | | 7(1+4x)=147 | | 4z^2-12z+13=0 | | w-15=4 | | 0=1.5x+x^1 | | -1+(-1.5)= | | 6(2x+5)= | | -3(-4x+2)=18 | | 3(10-3x)=120 | | x+1/4=5/8 | | 10-4x=6x-90 | | 0=16t^2-24t-1 | | x-33/7=2/3 | | 0=16t^2+24t+1 | | -7+4=-35 | | 14-7x=40-21x | | 3(9+6x)=9 | | -19x=57 | | N(t)=25t^3-25t^2+4t+2 | | H=16t^2+24t+1 | | -6n+2=-4n-14 | | 161-4x=23x+17 | | 14=2(x+7)-14 | | 2(x^2-3x+48)=0 | | 7x/4-2=10 | | 3vy-7v-9y+21=0 | | -2(6+8x)=100 | | 12-11=x/3 | | 5-10x=36-17x |

Equations solver categories